2019
DOI: 10.1002/ppsc.201900371
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Lipid‐Coated Persistent Luminescent Nanoparticles for In Vivo Imaging of Dendritic Cell Migration

Abstract: Dendritic cell (DC)‐based vaccines for immunotherapy have already achieved promising results in the last decade. To further improve current treatment protocols and enhance the therapeutic outcome, noninvasive in vivo tracking of DCs remains of crucial importance. Persistent luminescent nanoparticles (PLNPs) are inorganic materials which show an afterglow for hours after the optical excitation has ceased. If the afterglow is in the near‐infrared, the emission of injected particles can be tracked in vivo. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Organic NIR emitting molecules such as ICG (indocyanine green) are currently used in surgery [2,3], but these organic fluorophores are limited in terms of stability and are only used for direct imaging. In a recently developed imaging method, persistent luminescent particles are used, which are charged optically outside the body and are then injected [4]. While these particles keep emitting light for a long time in vivo without any additional excitation, such particles can emit only a limited amount of light, determined by the number of electronic traps that can be filled upon excitation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Organic NIR emitting molecules such as ICG (indocyanine green) are currently used in surgery [2,3], but these organic fluorophores are limited in terms of stability and are only used for direct imaging. In a recently developed imaging method, persistent luminescent particles are used, which are charged optically outside the body and are then injected [4]. While these particles keep emitting light for a long time in vivo without any additional excitation, such particles can emit only a limited amount of light, determined by the number of electronic traps that can be filled upon excitation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission. [ 73 ] (C) Schematic illustration of the PLL‐modified PLNPs for tracking of the transplanted hMSCs in bleomycin (BLM)‐induced PF. Reprinted with permission.…”
Section: Bioimaging Based On Modified Plmsmentioning
confidence: 99%
“…reported that they used lipid‐coated LiGa 5 O 8 :Cr 3+ PLNPs to achieve in vivo visualization of dendritic cells (DCs) migration which were used for immunotherapy. [ 73 ] Lipid modification greatly increased the biocompatibility and stability of PLNPs in biological media. After being injected into mice, DCs labeled with lipid‐coated PLNPs can be imaged for several days and the migration process from injection sites to lymph nodes was also monitored successfully (Figure 9B).…”
Section: Bioimaging Based On Modified Plmsmentioning
confidence: 99%
“…The pH of the mixture was adjusted to 8.0 with ammonia solution. The reaction solution was ultrasonicated at room temperature for 30 min and was stirred for a further 1.5 h. The turbid solution was transferred into a 50 mL Teflon-lined stainless steel autoclave and then heated at 220 °C for a certain period of time (12,24,36, and 48 h, respectively) for the hydrothermal reaction and cooled to room temperature. The resulting solution was centrifuged at 10000 rpm for 10 min and washed sequentially with ultrapure water and ethanol and then lyophilized.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…10,11 However, current PLNPs are limited to single-wavelength emission and are susceptible to a luminescence variation with time after stopping excitation, which has impeded the further development of PLNPs in bioimaging. 12,13 A dual-emissive probe can perform self-calibration reading and ratio imaging by detecting the fluorescence intensities at two different wavelengths, thereby effectively avoiding the interference of external factors. Dual-emissive PLNPs, therefore, are expected to achieve constant ratio imaging with a long detection window, promoting the biomedical applications of PLNPs.…”
Section: ■ Introductionmentioning
confidence: 99%